The Comparison of Models for Reducing Inhalant Allergen Level in House Dust of Urban and Rural Residents - Rofieq, Ainur; Latifa, Roimil; Fatmawati, Diani (International Journal of Engineering and Technology, 2019)
This current study aimed at: (1) describing the model for reducing inhalant allergen in house dust of urban and rural residents; (2) analyzing the different techniques of reducing inhalant allergen level in house dust of urban and rural residents.This study was employing descriptive comparative design. The objects of this study were models for reducing inhalant allergen level in house dust based on environment management in urban and rural residences. The stage was initiated by modifying conceptual models of urban and rural residences developed in the two previous studies by Rofieq (2015) and Rofieq (2014). Those modified models were expected to be operational models to be implemented by urban and rural residents. The next stage was comparing both operational models analytically. The results concluded that: there was a difference between the model of reducing inhalant allergen in house dust of urban and rural residents. The urban model was composed by multidimensional correlations of seven variables in residential areas, namely: education-economy, the ability to manage the house dust, house facilities, physical environment of houses, the characteristics of residents, chemical environment of house dust, and dust biotic. The rural model was composed of five variables, namely: the ability to manage the house dust, house facilities, the characteristics of residents, chemical environment of house dust, and dust biotic. Based on those two models, it was found that the technique of reducing inhalant allergen in house dust of urban residents was more complex than that of rural residents.Â Â